Investigating the effect of localized heat treatment and bioinspired structure on the crashworthiness of bumper subsystem - Israel Endale Asres; Ermias Gebrekidan Koricho; Ephrem Zeleke Kassa (Heliyon)
Particularly when they occur at high speeds, vehicle accidents represent a serious threat to human beings and due to this fact vehicle accident is considered as worlds high priority risk. Several research have been done to enhance the crashworthiness of bumper subsystems. With an emphasis on the major crash management system components which are also known as crash box and bumper beam, this study explores ways to improve the crashworthiness of vehicles. Two techniques were used, bio-inspired design for the bumper beam based on the false banana structure and localized heat treatment for the crash box. The study is conducted numerically using Explicit/dynamic analysis. New Car Assessment Program (NCAP) standard compliant numerical simulations were used to evaluate the performance of all the alternative models. For the selection of the best performing alternative model, complex proportional assessment method (COPRAS) is used. A baseline Peugeot 3008 model was used to test 26 different models for the crash box, taking into account variables such as heat treatment thickness and sequence of soft and hard pitch variation. The CB_22 model, which has constant soft and hard pitch, performed better. 10 alternative models which are mimicked from the false banana stem were considered for the bumper beam. When alternative models are compared to the Peugeot 3008 baseline, the fourth model (BD_04_900) with a reinforcement at 900 showed a 25 % improvement in terms priority value. The new bumper subsystem performed better in full-scale collision simulations than the Peugeot 3008 model, but it performed less in the 40 % offset crash scenario. In general, this research offers valuable insights for the automotive industry in developing safer and more efficient bumper sub systems. By conducting iterated localized heat treatment, incorporating bioinspired design principles, and considering the interdependent effects of different components, this study provides a valuable input for future advancements in vehicle safety design and standard.